The Influence of Link Duration on Supplier-Buyer Collaboration in the Automotive Industry: Lessons from Greater Jakarta, Indonesia - Syah, Donny Oktavian; Umemura, Tetsuo; Ricky, Christian (International Journal of Industrial Engineering and Management, 2024)
This exploratory study investigates the association between technology transfer, technical exchange, and supplier performance within Greater Jakarta, Indonesia, focusing on the moderating role of link duration in the buyer-supplier relationship in the automotive industry. The data collection involved site visits and the administration of Likert-scale questionnaires to middle to upper-level management personnel responsible for relevant processes. The sampled population comprised 99 companies, including six assembler companies, 59 tier-1 companies, and 34 tier-2 companies. Smart PLS 3.2.7 software was employed to conduct partial least squares multi-group analysis (PLS-MGA) to process and analyze the data. The analysis was divided into two groups: the first exploration consisted of buyer-supplier relationships of less than five years and more than five years. Next, the second exploration consisted of buyer-supplier relationships of less than and more than ten years. The findings revealed that technology transfer has significant importance in relationships lasting over five but less than ten years, while technical exchange becomes significant in relationships exceeding five years. The research contributes valuable insights into the dynamics of supplier-buyer collaboration in the automotive industry, particularly in Indonesian context. Article history: Received (May 14, 2023); Revised (November 15, 2023); Accepted (January 10, 2024); Published online (January 23, 2024)